Programa Educa, televisión para aprender y su incidencia en el proceso de aprendizaje en las niñas de 10 y 11 años del séptimo año de educación básica de la Unidad Educativa Amelia Gallegos Díaz en el periodo febrero - agosto de 2015 - Rigcha Sinchi, Ana Julia (2015)
This research project entitled: "Educate, television to learn and their impact on the learning process in girls 10 and 11 years of the seventh year of basic education Education Unit Amelia Gallegos Diaz in the period February - August 2015 "is divided into four chapters; In the first chapter, the problem statement is pointed out, the objectives of both: general and specific justification and importance of the subject is also presented. The second chapter covers the frame of reference, where scientific collections of the various issues identified in the draft as are exposed: television, educational program, "Educate, television to learn", television and education program and television educational program in the process learning in children, the same as are developed under theoretical basis for accuracy in content. It also covers the hypothesis, both variables, dependent and independent and operationalization of them are identified. In the third chapter everything related to methodological framework it is developed, ie the method, type and design gives the research also population and sample our research project is specified and the processing and discussion of results is detailed, along with the hypothesis testing and finally obtaining data presented through statistical tables and graphs. the conclusions and recommendations that have been reached by the results obtained in the research process set out in the fourth and final chapter.